The truth about exercise addiction : understanding the dark side of thinspiration - Schreiber, Katherine, 1988-; Hausenblas, Heather A. (Lanham : Rowman & Littlefield, 2015)
Designed for individuals concerned about their workout habits, personal trainers, family and friends of those with a problem, as well as working mental health professionals treating exercise addicts, [this book] provides an easy-to-read, illuminating glimpse into the rising trend of over-exercise. Delving into the history of exercise addiction and the growing influence of "thinspiration," Katherine Schreiber and Heather A. Hausenblas illustrate the symptoms and dangers of obsessive exercise with true stories from sufferers, all while exploring why and how such a seemingly healthy behavior morphs into a dangerous means of self-destruction. Analyzing the causes and consequences of excessive physical activity alongside the influence of genetics, culture, and personality, this book allows readers to gain a greater understanding of what exercise addiction looks and feels like. The Truth About Exercise Addiction also provides an unprecedented list of resources to address exercise addiction, a snapshot of treatments currently available for sufferers, and guidelines on how to confront and care for someone who may have a problem. -- Front jacket flap.
What it is : defining exercise addiction -- What it looks like : the signs and symptoms of exercise addiction -- Who coined it? : a brief history of exercise addiction -- How it begins : the origins of exercise addiction -- What it does : the short- and long-term health risks of exercise addiction -- Why it happens : thinspiration's dark side -- What it feels like : exercise addicts' true stories -- What to do about it : treatment -- How to approach someone with a problem -- Frequently asked questions -- Appendix A: How to get help : where to go, what to read, and to whom to reach out -- Appendix B: Common exercise addiction measures.
Includes bibliographical references (pages 223-236) and index.
Keywords: Exercise addiction; Eating disorders